Early education and counselling of patients with acute coronary syndrome. A pilot study for a randomized controlled trial. (June 2016) - Weibel, Lukas; Massarotto, Paola; Hediger, Hannele; Mahrer-Imhof, Romy
Background: At time of discharge, patients with acute coronary syndrome often have a knowledge deficit regarding their disease, further treatment and necessary behavioural changes. It is well known that self-efficacy as a prerequisite for behavioural changes can be influenced by patient education. This study investigated whether an individualized education programme starting early in the cardiac care unit enhanced self-efficacy and rehabilitation programme attendance, and was feasible and satisfying for patients. Methods and design: In a pilot randomized controlled trial, 40 patients with acute coronary syndrome were enrolled. The intervention group received in addition to standard care an early individual needs-oriented educational session in the cardiac care unit and subsequently one on the ward addressing risk factors, medication and self-management as well as referral to a rehabilitation programme by a nurse. Self-efficacy was assessed twice, at attendance in a rehabilitation programme six weeks after discharge. The participants' satisfaction with the intervention was assessed qualitatively. Results: When controlling for anxiety and depression, the intervention group showed significant better self-efficacy scores on the ability to control the symptoms ( p =0.034). When controlling additionally for age, no significant differences could be detected. The attendance of a rehabilitation programme was higher in the intervention group. The participants in the intervention group reported high satisfaction with the early education. Conclusion: Early education seems to benefit patients with acute coronary syndrome. In light of increased confidence to control one's symptoms and the higher attendance in rehabilitation programmes, as well as a high satisfaction with the intervention, a full powered study will be pursued.